2010
DOI: 10.3189/002214310791968430
|View full text |Cite
|
Sign up to set email alerts
|

Backwasting rate on debris-covered Koxkar glacier, Tuomuer mountain, China

Abstract: A physically based energy-balance model with improved parameterization of solar radiation for a sloped ice surface has been developed to estimate the backwasting rate of an ice cliff in a debris-covered area. The model has been tested against observations between 5 August and 5 September 2008 on 38 ice cliffs in the debris-covered area of Koxkar glacier, Tuomuer mountain, China. We calculated that the energy-balance model gave a good estimate of the backwasting rates, with errors in the range ±1.96 cm d−1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 28 publications
6
89
1
Order By: Relevance
“…Moreover, our data showed that the transformations even within one moraine complex were not uniform in time and space, and that the sites which are active in one season can be almost completely stable in the next. To sum up, the results from Ebbabreen and Ragnarbreen are higher than previously reported from Svalbard, and are also higher than or of similar magnitude to the values reported from different climatic zones such as Iceland, the Himalayas and the European Alps (Krüger and Kjaer, 2000;Benn et al, 2001;Kjaer and Krüger, 2001;Han et al, 2010;Pelfini et al, 2012). Together with the evidently high local variability in dead-ice melting and sediment redisposition, it confirms the suggestion of Schomacker (2008) that these processes are more related to local factors such as topography and abundance of meltwater than climatic conditions.…”
Section: Comparison With Short-term Dead-ice Melting Ratescontrasting
confidence: 28%
“…Moreover, our data showed that the transformations even within one moraine complex were not uniform in time and space, and that the sites which are active in one season can be almost completely stable in the next. To sum up, the results from Ebbabreen and Ragnarbreen are higher than previously reported from Svalbard, and are also higher than or of similar magnitude to the values reported from different climatic zones such as Iceland, the Himalayas and the European Alps (Krüger and Kjaer, 2000;Benn et al, 2001;Kjaer and Krüger, 2001;Han et al, 2010;Pelfini et al, 2012). Together with the evidently high local variability in dead-ice melting and sediment redisposition, it confirms the suggestion of Schomacker (2008) that these processes are more related to local factors such as topography and abundance of meltwater than climatic conditions.…”
Section: Comparison With Short-term Dead-ice Melting Ratescontrasting
confidence: 28%
“…The importance of ice cliffs has become increasingly clear (Sakai et al, 1998;Han et al, 2010;Sakai et al, 2002;Watson et al, 2017), but the mapping of these features remains a challenge, especially at spatial scales beyond a few glaciers. The map-view surface expression of an ice cliff is often a crescent, circular or linear swath of steep, bare (or thinly debris-covered) glacier ice surrounded by a debris layer.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…The mechanism(s) of ice cliff formation, the controls of ice cliff migration patterns and ice cliff residence time on a glacier are gaining research attention but are still poorly understood processes, in part, due to a lack of base data (Reid and Brock, 2014;Watson et al, 2017). Melt and surface energy fluxes at specific ice cliffs have been studied in detail (Sakai et al, 1998;Han et al, 2010;Sakai et al, 2002;Reid and Brock, 2014;Buri et al, 2016a) and digital elevation model (DEM) differencing has shown the spatial trends of enhanced glacier melt relative to surrounding debris cover and ice cliff evolution at the scale of several cliffs or a single glacier tongue (Thompson et al, 2016;Brun et al, 2016). All of the studies mentioned suggest that ice cliffs, if present on a debris-covered glacier, need to be accounted for in order to adequately model glacier mass loss and response to climate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of ice cliffs and supraglacial lakes are another unique characteristic of glaciers ( Figures 5 and 6) as both of these features are associated with high-magnitude ablation, and ice cliffs contribute considerably to the overall ablation of a glacier even though they often cover only a small percentage of the glacier surface [120,[134][135][136][137]. Theoretically, these features and glacier ablation form a positive feedback loop-an ice cliff exposes clean ice while supraglacial lakes exhibit low albedo both of which increase ablation.…”
Section: Ice Cliffs and Supraglacial Lakesmentioning
confidence: 99%